Hypertension as an effect modifier for preterm and small for gestational age births in migrant women in Belgium: A population-based study - Clotilde Lamy; Amira Doghri; Elena Costa; Michel Boulvain; Alice Hocquette; Sophie Alexander; Judith Racapé (PLoS ONE, 2025)
Background The association between migration and pregnancy outcomes gives contradictory results. Women’s socio-economic status explains some differences, but its influence may vary according to women’s underlying health conditions. Our aim was to understand how comorbidities modify the relationship between migration and preterm birth or small for gestational age in Belgium. Methods Data are related to all singleton births to women living in Belgium between 2010 and 2019 (n = 1 200 417). Maternal nationalities were grouped as Belgium, European Union, Eastern Europe, North Africa, Sub-Saharan Africa and the Middle East. A logistic regression was used to estimate the association between maternal nationalities and perinatal outcomes, taking into account the socio-economic status and maternal comorbidities: hypertension, obesity, and diabetes. The interaction effect between maternal nationalities and comorbidities was tested. Results Migrant women were more socio-economically disadvantaged than Belgian women. All migrant women without hypertension had a significantly lower Odd Ratio of preterm birth and small for gestational age than Belgian (p < 0.001). In contrast, women with hypertension had a higher OR than Belgian women, even after adjustment for socio-economic status and other comorbidities. This difference was more striking among Sub-Saharan African and Middle Eastern women: respectively, aORs 1.45 (95%CI 1.30–1.62) and 1.24 (95%CI 1.01–1.54) for preterm birth, and aORs 1.17 (95%CI 1.03–1.17) and 1.28 (95%CI 1.02–1.60) for small for gestational age. Conclusions Hypertension modifies the association between migration and unfavourable pregnancy outcomes. Although migrant women had a lower risk of preterm birth and small for gestational age than Belgian women, in the presence of hypertension, their risk was significantly higher than Belgian women with the same conditions. Further research is needed to analyse the complex relationships between migration, social status, women’s living conditions, and perinatal outcome.